The Importance of the Role of Parents and Teachers as Moral Role Models in Early Childhood Education - Perwitasari, Nur Aini; Syarafina, Nissa Azzahra; Qurratu’ain, Nisrina; Putri, Alia; Rasi’in, Rasi’in (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Early Childhood Education (ECE) plays a vital role in shaping a child's character and morals, especially during the golden age period which is the peak time for development. This research aims to examine the importance of the role of parents and teachers as moral role models in early childhood education. The method used is a literature review (library research) by examining relevant literature, such as journals and scientific articles. The results of the study show that parents are the main role models in the family who, through emotional closeness and positive parenting styles, are capable of instilling moral and spiritual values in children. Meanwhile, teachers act as role models in the school environment, reinforcing the moral values that have been taught at home through their daily attitudes, words, and actions. Cooperation between parents and teachers is essential to create a conducive, consistent, and harmonious educational environment. Forms of cooperation include education, nurturing, effective communication, parental involvement in school activities, and monitoring the child's moral development. In conclusion, the role of both parents and teachers as moral role models is very important to shape a generation that is not only intellectually smart but also of noble character.